The Role of Macrophages in Acute and Chronic Wound Healing and Interventions to Promote Pro-wound Healing Phenotypes - Krzyszczyk, Paulina; Schloss, Rene; Palmer, Andre; Berthiaume, François (Frontiers in Physiology, 2018)
Macrophages play key roles in all phases of adult wound healing, which are inflammation, proliferation and remodeling. As wounds heal, the local macrophage population transitions from predominantly pro-inflammatory (M1-like phenotypes) to anti-inflammatory (M2-like phenotypes). Non-healing chronic wounds, such as pressure, arterial, venous and diabetic ulcers indefinitely remain in inflammation—the first stage of wound healing. Thus, local macrophages retain pro-inflammatory characteristics. This review discusses the physiology of monocytes and macrophages in acute wound healing and the different phenotypes described in the literature for both in vitro and in vivo models. We also discuss aberrations that occur in macrophage populations in chronic wounds, and attempts to restore macrophage function by therapeutic approaches. These include endogenous M1 attenuation, exogenous M2 supplementation and endogenous macrophage modulation/M2 promotion via mesenchymal stem cells, growth factors, biomaterials, heme oxygenase-1 (HO-1) expression and oxygen therapy. We recognize the challenges and controversies that exist in this field, such as standardization of macrophage phenotype nomenclature, definition of their distinct roles and understanding which phenotype is optimal in order to promote healing in chronic wounds.